Des occupations laténiennes sur le plateau de Champeigne tourangelle, communes d’Athée-sur-Cher et de Truyes (Indre-et-Loire) - Fabrice Couvin; Sandrine Linger-Riquier; Gaëlle Robert; Gwenaël Roy (Revue Archéologique du Centre de la France)
The Champeigne tourangelle plateau is located between the valleys of the Cher and the Indre. In an area of less than 2.5 km2, three excavations of the A85 motorway and the evaluation of a carry, at Athée-sur-Cher and Truyes (Indre-et-Loire), have delivered late Iron Age settlements. If these finds provide a vision of the density of the territorial occupation at the end of the Gallic period, prior and posterior remains provide also data related to the evolution of the plateau from late Protohistory to the Roman period.